Biological and molecular characterization of bidens mosaic virus infecting patchouli (Pogostemon cablin) in Brazil - Martines, Caroline da Cruz [UNESP]; Favara, Gabriel Madoglio [UNESP]; Marubayashi, Julio Massaharu [UNESP]; Dovigo, Leonardo Hipólito [UNESP]; Nogueira, Angélica Maria [UNESP]; Kitajima, Elliot Watanabe; Krause-Sakate, Renate [UNESP] (Wiley, 2024)
Six patchouli (Pogostemon cablin Benth.) plants showing symptoms of viral infection were found in Brazil. Transmission electron microscopy revealed flexuous particles and characteristic pinwheel-shaped cytoplasmic inclusions of potyvirus in sap and cells of symptomatic leaves. Potyvirus infection was confirmed through RT-PCR, using universal primers followed by nucleotide sequencing. The obtained sequences, comprising part of the CP gene and the 3′ non-translated region, showed 97.71%–97.87% identity with an isolate of bidens mosaic virus (BiMV). The nucleotide sequences of the CP, HC-Pro and CI genes of BiMV isolates from patchouli plants were obtained through RT-PCR with specific primers followed by nucleotide sequencing. The obtained sequences showed 95.78%–97.1% identities with BiMV isolates from Brazil. One BiMV isolate from a patchouli infected plant was sap-transmitted to different plant species. Chenopodium amaranticolor exhibited local lesions, Bidens pilosa developed leaf mosaic, and Nicotiana benthamiana exhibited chlorosis and stunting. The BiMV isolate was transmitted from infected patchouli plant to B. pilosa using Myzus persicae aphids. This is the first confirmation of patchouli infected with BiMV in Brazil. Further studies are necessary to assess the incidence of this potyvirus in commercial patchouli crops, as well as the damage caused to plant development and the quantity and quality of essential oils produced.
Keywords: BiMV; essential oil; potyviruses; viral infection